Inequality and stagnation by policy design: Mainstream denialism and its dengerous political consequences - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
This paper argues the mainstream economics profession is threatened by theories of the financial crisis and ensuing stagnation that attribute those events to the policies recommended and justified by the profession. Such theories are existentially threatening to the dominant point of view. Consequently, mainstream economists resist engaging them as doing so would legitimize those theories. That resistance has contributed to blocking the politics and policies needed to address stagnation, thereby contributing to a political vacuum which is being filled by odious forces. Those ugly political consequences are unintended, but they are still there and show the dangerous consequences of the death of pluralism in economics. The critique of mainstream economists is not about "values" or lack of "change": it is about academic practice that suppresses ideas which are existentially threatening.
Keywords: A0; A11; B50; E00; E12; 330; Income inequality; stagnation; neoliberalism; Keynesianism; pluralism